2007
DOI: 10.3758/bf03195938
|View full text |Cite
|
Sign up to set email alerts
|

Graded motor responses in the time course of categorizing atypical exemplars

Abstract: The time course of categorization was investigated in four experiments, which revealed graded competitive effects in a categorization task. Participants clicked one of two categories (e.g., mammal or fish) in response to atypical or typical exemplars (e.g., whale or cat) in the form of words (Experiments 1 and 2) or pictures (Experiments 3 and 4). Streaming x, y coordinates of mouse movement trajectories were recorded. Normalized mean trajectories revealed a graded competitive process: Atypical exemplars produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
296
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(305 citation statements)
references
References 76 publications
6
296
0
3
Order By: Relevance
“…Researchers have looked to realtime hand movements, as we did here using mouse tracking, to flesh out the interactive and continuously evolving nature of mental processes. Such work has found evidence for the continuous dynamics in spoken language processing (Spivey, Grosjean, & Knoblich, 2005), semantic categorization (Dale, Kehoe, & Spivey, 2007), and visual search (Song & Nakayama, 2008), among others (Spivey, 2007). We believe that a dynamic approach to social perception and cognition could be similarly insightful (e.g., Freeman et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have looked to realtime hand movements, as we did here using mouse tracking, to flesh out the interactive and continuously evolving nature of mental processes. Such work has found evidence for the continuous dynamics in spoken language processing (Spivey, Grosjean, & Knoblich, 2005), semantic categorization (Dale, Kehoe, & Spivey, 2007), and visual search (Song & Nakayama, 2008), among others (Spivey, 2007). We believe that a dynamic approach to social perception and cognition could be similarly insightful (e.g., Freeman et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Such a dynamic continuity account, integral to an emergent continuity of mind framework (Spivey, 2007;Spivey & Dale, 2004) rooted in the dynamical systems approach to cognitive science (Port & van Gelder, 1995) and attractor neural network models, argues that perceptual-cognitive processing exhibits continuous-and not discrete-changes in the salience of multiple simultaneously activated representations. Indeed, growing evidence for the continuous dynamics in real-time cognition (Dale, Kehoe, & Spivey, 2007;Farmer, Anderson, & Spivey, 2007;Spivey, 2007;Spivey & Dale, 2004Spivey, Grosjean, & Knoblich, 2005;Spivey, Richardson, & Dale, in press) suggests that, across the course of a given cognitive process, as the cognitive system dynamically approximates one of competing mental states (e.g., Male or Female), it entertains a graded mixture of partially consistent representations that continuously flow into-rather than discretely arrive at-a stable response (e.g., "I see a male! ").…”
mentioning
confidence: 99%
“…Various behavioral techniques have been used to provide indirect evidence for this dynamic flux of partial and simultaneous activation of multiple representations, which continuously cascade into later processing stages and gradually settle on eventual categorical outcomes (see Dale et al, 2007;Spivey & Dale, 2004). Most of these techniques involve continuous real-time measures, such as online hand movements (e.g., Dale et al, 2007;Spivey & Dale, 2004Spivey et al, in press) and eye movements (e.g., McMurray, Tannenhaus, Aslin, & Spivey, 2003;Spivey, Tanenhaus, Eberhard, & Sedivy, 2002).…”
mentioning
confidence: 99%
“…Mouse tracking tasks have recently been used across a range of domains, including speech sound categorization (Farmer, Liu, Mehta, & Zevin, 2009), syntactic processing (Farmer, Anderson, & Spivey, 2007;Farmer, Cargill, Hindy, Dale, & Spivey, 2007), semantic categorization (Dale, Kehoe, & Spivey, 2007), attention-related processes (Hindy, Hamilton, Houghtling, Coslett, & Thompson-Schill, 2009), evaluative thinking (Dale & Duran, 2011;McKinstry, Dale, & Spivey, 2008), deceptive responding (Duran, Dale, & McNamara, 2010;Duran, Roche, Snyder, & McCall, 2008), and social perception and judgment (e. g. Freeman & Ambady, 2009;Freeman, Ambady, Rule, & Johnson, 2008;Wojnowicz, Ferguson, Dale, & Spivey, 2008). Stated broadly, experimental results have consistently demonstrated that arm movements (as measured by the movement trajectories of the computer mouse or other devices) systematically reflect ongoing cognitive processes in a wide range of tasks (for reviews of this literature, see Freeman, Dale, & Farmer, 2011;Song & Nakayama, 2009).…”
Section: Computer-mouse Tracking and The Dynamics Of Response Selectionmentioning
confidence: 99%